Regioisomeric Benzidine‐Fullerenes: Tuning of the Diverse Hole‐Distribution to Influence Charge Separation Patterns. (2nd March 2023) - Wang, Chong; Wu, Bo; Li, Yang; Dong, Tianyang; Chai, Yongqiang; Zhang, Yuhe; Wang, Chunru
Abstract: Understanding the influence of molecular structure on charge distribution and charge separation (CS) provides essential guidance for optoelectronic materials design. Here we propose a regioisomeric strategy to tune the diverse hole‐distribution, and probe the influence on CS patterns. Para‐, meta‐ and ortho‐ substituted benzidine‐fullerene, named 1 p, 1 m and 1 o are designed. Following CS, hole‐delocalization occurs in 1 p, while hole‐localization exists in 1 m and 1 o . The rates of charge separation (4.02×10 11  s −1 ) and recombination (9.8×10 9  s −1 ) of 1 p is about 20 and 12 times faster than 1 m and 1 o, indicating that para‐ determined delocalization promotes ultrafast CS, while meta‐ and ortho‐ generated localization contributes to long‐lived CS states. Computational analysis further implies that localization results from the destruction of electronic conjugation for 1 m, and limitation of conformational relaxation for 1 o . Given that the universality and simplicity of regional isomerism, this work opens up new thoughts for molecular design with tunable charge separation patterns. Abstract : Three regioisomeric benzidine‐fullerenes have been synthesized. Following charge separation (CS), the para ‐isomer manifests hole‐delocalization, promoting ultrafast CS; while meta ‐ and ortho ‐isomers cause hole‐localization, contributing to long‐lived CS state. This work reveals the influence of regioisomerism on charge distribution and CS.